Proteomic profiling of eIF3a conditional knockout mice - Zhuo, Wei; Chen, Juan; Jiang, Shilong; Zheng, Juyan; Huang, Hanxue; Xie, Pan; Li, Wei; Lei, Mengrong; Yin, Jiye; Gao, Ying; Liu, Zhaoqian (Frontiers in Molecular Biosciences, 2023)
eIF3a is the largest subunit of the eukaryotic translation initiation factor 3 (eIF3) and plays an integral role in protein biosynthesis, impacting the onset, development, and treatment of tumors. The proteins regulated by eIF3a are still being explored in vivo. In this study, a Cre-loxP system was used to generate eIF3a conditional knockout mice. A TMT-labeling-with-LC-MS/MS analysis was employed to identify differentially expressed proteins in fat, lung, skin, and spleen tissue from the eIF3a knock-out mice and controls. Bioinformatics analysis was then used to explore the function and molecular signaling pathways of these protein landscapes. We observed that eIF3a is essential for sustaining life and even for the development and maturation of an individual. Abnormal tissue pathology was found in the lungs, fat, skin, spleen, and thymus. When compared to the control, 588, 210, 324, and 944 differentially expressed proteins were quantified in the lungs, fat, skin, and spleen, respectively, of the eIF3a knock-out mice. These differently expressed proteins were tissue-specific, with only 8 proteins shared by the four tissues. Bioinformatics analysis has uncovered a broad range of functions for eIF3a, from cellular signaling pathway, immune response, and metabolism to xenobiotic substrate processing. In particular, we have identified several pathways related to oxidative stress in the KEGG database, including nitrogen metabolism, peroxisome, cytochrome P450 drug metabolism, pyruvate metabolism, PPAR signaling pathway, phospholipase D signaling pathway, B-cell receptor signaling pathway, ferroptosis, and focal adhesion. Our findings show that eIF3a is an essential gene for sustaining life, and its downstream proteins are involved in a myriad of novel functions beyond mRNA translational regulation.